2016
DOI: 10.1016/j.electacta.2016.04.174
|View full text |Cite
|
Sign up to set email alerts
|

The long-range effect induced by untying hydrogen bonds for single cell test using SECM

Abstract: The enhanced positive feedback current of scanning electrochemical microscopy (SECM) is observed at a large separation between the tip and the substrate surface in the case of a 3-mercaptopropionic acid (3-MPA) self-assembled monolayer (SAM). The effect that induces the large separation (named the long-range effect) is confirmed by SECM and quantitatively studied by electrochemical quartz crystal microbalance (EQCM). A key finding is that the long-range effect results from untying hydrogen bonds beforehand for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 36 publications
1
13
0
2
Order By: Relevance
“…前面介绍了探针电极上MPA与二茂铁甲醇之间 图 1 在MPA SAM电极上的分子间氢键可逆组装与解组装 过程示意图 [22] (网络版彩图) [22] (网络版彩图) 图 3 存在分子间氢键情况下二茂铁甲醇的电化学氧化过程示意图(红色峰: 氢键键合二茂铁甲醇的峰; 蓝色峰: 非氢键键合 二茂铁甲醇的峰) [23] (网络版彩图) [29] (网络版彩图) [29] (网络版彩图) 图 8 分子间氢键诱导"长程效应"的机理示意图 [34] Figure 8 Schematic representation of the mechanism of the longrange effect which induced by the intermolecular hydrogen bond [34]. 图 9 探针向不同基底的渐近曲线图.…”
Section: Sam表面分子间氢键的定量研究unclassified
See 2 more Smart Citations
“…前面介绍了探针电极上MPA与二茂铁甲醇之间 图 1 在MPA SAM电极上的分子间氢键可逆组装与解组装 过程示意图 [22] (网络版彩图) [22] (网络版彩图) 图 3 存在分子间氢键情况下二茂铁甲醇的电化学氧化过程示意图(红色峰: 氢键键合二茂铁甲醇的峰; 蓝色峰: 非氢键键合 二茂铁甲醇的峰) [23] (网络版彩图) [29] (网络版彩图) [29] (网络版彩图) 图 8 分子间氢键诱导"长程效应"的机理示意图 [34] Figure 8 Schematic representation of the mechanism of the longrange effect which induced by the intermolecular hydrogen bond [34]. 图 9 探针向不同基底的渐近曲线图.…”
Section: Sam表面分子间氢键的定量研究unclassified
“…图 9 探针向不同基底的渐近曲线图. 黑线: 金基底, 含二茂 铁甲醇的电解液; 红线: 绝缘基底, 含二茂铁甲醇的电解液; 蓝线: MPA SAM修饰的金基底, 含二茂铁甲醇的电解液; 绿 线: MPA SAM修饰的金基底, 含亚铁氰化钾的电解液; 电解 液pH均为6.4 [34] (网络版彩图) [34] (网络版彩图) 图 11 SECM的SG/TC模式中MPA SAM表面氢键向静电转 变过程的示意图 [37] (网络版彩图) 图 13 SECM反馈模式探究SAM表面阳离子开关示意图 [38] (网络版彩图) [39] (网络版彩图) 图 15 基于电荷翻转的天冬氨酸和精氨酸分子识别原理示意图 [39] (网络版彩图) [39] (网络版彩图)…”
Section: Sam表面分子间氢键的定量研究unclassified
See 1 more Smart Citation
“…19−22 We previously demonstrated that the intermolecular hydrogen bonding exists between the redox species ferrocenylmethanol (FcCH 2 OH) and 3-mercaptopropionic acid (MPA). 23 More recently, we reported on the use of cyclic voltammetry as platforms for regulating the intermolecular hydrogen bonding between FcCH 2 OH and MPA in which we found the features of the cyclic voltammetry were complicated by intermolecular hydrogen bonding. 24 As the amount of transferred electrons devoted to the anodic peak or cathodic peak of cyclic voltammogram is related to amount of the redox species involved in the electrochemical process, 25,26 we intend to quantify the amount of intermolecular hydrogen bonding in the above-mentioned molecular recognition model by interpreting the slight changes of cyclic voltammogram.…”
Section: ■ Introductionmentioning
confidence: 96%
“…More details about EQCM measurement can be found in our previous work. 23 The increased mass (m) of MPA SAM on gold was measured by Sauerbrey's equation, seen below, where A is the surface area of the gold electrode (A = 0.2 cm 2 ), ρ is the density of quartz, μ is the shear modulus of quartz, and F is the inherent frequency (9 MHz) of the quartz crystal. The absolute value of the frequency change (ΔF) has been used as an indicator of surface coverage of the MPA monolayer; thus, ΔF is increasing along with the addition of mass.…”
Section: ■ Introductionmentioning
confidence: 99%